Molded article that can be laser welded and laser marked
Patent Information
- Application Number
- CN201880080060.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-12-12
- Filing Date
- 2018-12-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2038-12-10
AI Technical Summary
其中,振动焊接、超声波焊接可能因振动而造成内部的电子部件等损坏,因此在内部收纳精密的电子部件等的壳体用途等中并不适用
[0021] According to the present invention, it is possible to provide molded articles that combine laser welding and laser marking capabilities.
Smart Images

Figure BDA0002534655270000121 
Figure BDA0002534655270000131
Abstract
Description
Technical Field
[0001] This invention relates to molded articles capable of both laser welding and laser marking. Background Technology
[0002] Generally, molded articles formed from resin compositions are ultimately used in combination with other components. When these articles are combined with other components, as methods of integration, besides physical structural fittings such as screwing, fastening, and riveting, techniques such as secondary molding, bonding, and welding are known. Screwing and bonding require additional components such as screws and adhesives, and the processes of joining and bonding them are time-consuming and labor-intensive. Furthermore, fastening and riveting require specific structures within the molded article, creating design constraints. Secondary molding also requires consideration of fit in the design and special metal molds for positioning the primary molded article. Welding is useful in addressing these drawbacks. Laser welding, vibration welding, and ultrasonic welding are known as welding methods. However, vibration welding and ultrasonic welding can damage internal electronic components due to vibration, making them unsuitable for applications such as housings containing delicate electronic components. Laser welding, which does not generate vibration, is preferred for such applications.
[0003] Laser welding is a technique in which a molded article formed of a material that is transmissible to laser beams is overlapped with a molded article formed of a material that absorbs laser beams, and a laser beam is irradiated from the side of the transmissible molded article, causing the interface between the transmissive and absorbent molded articles to exotherm and weld (see Patent Document 1). Furthermore, the resin composition used in the molded article for this application is required to have the property of being weldable by irradiation with a laser beam (laser weldability).
[0004] On the other hand, as molded products, product information is often printed or depicted on the surface of the molded product to facilitate design, information display, and component identification during assembly. Furthermore, from a reliability standpoint, laser marking can sometimes be used when long-term visibility is required (see, for example, Patent Document 2). Known methods for laser marking include: irradiating uncolored or light-colored molded products with a laser beam to carbonize the resin and thus perform black marking; pre-adding a compound that will develop color through the energy of a laser beam and then marking it by that compound; and irradiating molded products colored black or dark colors with a laser beam to sublimate (decompose) and decolorize the colorant (carbon black) (revealing the base color of the resin composition).
[0005] It would be useful to have molded articles that combine the laser welding and laser marking properties described above. Here, it is possible to consider giving molded articles laser welding properties such that, for molded articles colored with carbon black, marking can be performed by sublimating and decolorizing the carbon black using a laser beam. In this case, carbon black is used for coloring and decolorizing in laser marking, and as an exothermic medium in laser welding to impart laser beam absorption properties to the material.
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent Application Publication No. 2008-24946
[0009] Patent Document 2: Japanese Patent Application Publication No. 11-140284 Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] In laser marking, carbon black that is not easily sublimated is preferred. However, if carbon black is too easily sublimated, it will sublimate during the period before the exothermic heat required for resin melting is obtained in laser welding, making it difficult to achieve a welded bond. Laser welding requires the carbon black to be retained at least until the resin melting temperature is reached. Alternatively, even with easily sublimable carbon black, it is possible to retain it by adding a large amount until the exothermic heat required for laser welding is obtained. However, from the viewpoint of laser marking, the laser irradiation dose needs to be increased accordingly to allow a large amount of carbon black to sublimate and decolorize. As a result, overheating the resin can cause discoloration of the resin portion due to carbonization and deterioration, leading to reduced visibility of the laser marking. This is especially problematic when laser marking easily carbonized resins such as aromatic resins, where visibility is easily reduced due to discoloration of the resin portion.
[0012] Based on the above, there is a trade-off between visibility and bond strength in laser marking and laser welding due to the influence of carbon black. Therefore, it is impossible to make a finished product possess both laser marking and laser welding properties using conventional methods.
[0013] The present invention was made in view of the above-mentioned existing problems, and its object is to provide molded articles that combine laser welding and laser marking properties.
[0014] Methods for solving problems
[0015] One aspect of the present invention that solves the aforementioned problems is as follows.
[0016] (1) A molded article that can be used on the laser beam absorption side during laser welding, and can be marked by irradiating a laser beam.
[0017] The molded article is formed from a resin composition, and the resin composition contains, relative to 100 parts by weight of thermoplastic aromatic resin, a primary particle size of 20-40 nm and a DBP oil absorption of 100 cm³. 3 0.1 to 0.4 parts by weight of carbon black per 100g or more.
[0018] (2) In the molded article described in (1) above, the thermoplastic aromatic resin is polybutylene terephthalate resin or polyarylene sulfide resin.
[0019] (3) In the molded article described in (1) or (2) above, relative to 100 parts by weight of thermoplastic aromatic resin, it further includes 20 to 200 parts by weight of inorganic filler and 10 to 30 parts by weight of elastomer.
[0020] Invention Effects
[0021] According to the present invention, it is possible to provide molded articles that combine laser welding and laser marking capabilities. Detailed Implementation
[0022] The molded article of this embodiment is characterized in that it is a molded article that can be used on the laser beam absorption side during laser welding, and can be marked by irradiating a laser beam. The molded article is formed from a resin composition, and relative to 100 parts by weight of thermoplastic aromatic resin, the resin composition contains a primary particle size of 20-40 nm and a DBP oil absorption of 100 cm³. 3 0.1 to 0.4 parts by weight of carbon black per 100g or more.
[0023] Hereinafter, the components of the resin composition constituting the molded article of this embodiment will be described first.
[0024] [Thermoplastic Aromatic Resins]
[0025] The thermoplastic aromatic resin used in this embodiment is a thermoplastic resin having aromatic groups in its structural units. It is an easily carbonizable resin, i.e., an aromatic resin, and aims to achieve both laser weldability (used as a molded article with laser beam absorption) and laser marking capability in molded articles formed from resin compositions using such resins. Hereinafter, polybutylene terephthalate resin (hereinafter also referred to as "PBT resin") and polyarylene sulfide resin (hereinafter also referred to as "PAS resin") are listed as such resins for description, but this embodiment is not limited to these.
[0026] (Polybutylene terephthalate resin)
[0027] PBT resin is a resin obtained by polycondensation of a dicarboxylic acid component containing at least terephthalic acid or its ester-forming derivatives (C1-6 alkyl esters, acyl halides, etc.) and a diol component containing at least 4 carbon atoms (1,4-butanediol) or its ester-forming derivatives (acetylations, etc.). PBT resin is not limited to homopolymer butylene terephthalate, but can also be a copolymer containing 60 mol% or more (especially 75 mol% or more and 95 mol% or less) butylene terephthalate units.
[0028] The amount of terminal carboxyl groups in the PBT resin is not particularly limited, provided it does not impair the effectiveness of the invention. Preferably, the amount of terminal carboxyl groups in the PBT resin is 30 meq / kg or less, more preferably 25 meq / kg or less.
[0029] The intrinsic viscosity (IV) of the PBT resin is preferably 0.65 to 1.20 dL / g. When using PBT resin with an intrinsic viscosity within this range, the resulting resin composition exhibits particularly excellent mechanical properties and flowability. Conversely, if the intrinsic viscosity is less than 0.65 dL / g, excellent mechanical properties cannot be obtained, and if it exceeds 1.20 dL / g, excellent flowability may not be achieved.
[0030] Furthermore, PBT resins with intrinsic viscosities within the aforementioned range can be blended with PBT resins having different intrinsic viscosities to adjust their intrinsic viscosity. For example, by blending PBT resins with intrinsic viscosities of 0.9 dL / g and 0.7 dL / g, a PBT resin with an intrinsic viscosity of 0.8 dL / g can be prepared. The intrinsic viscosity (IV) of the PBT resin can be measured, for example, in o-chlorophenol at a temperature of 35°C.
[0031] In PBT resin, dicarboxylic acid components (comonomer components) other than terephthalic acid and its ester-forming derivatives can include, for example, C8-14 aromatic dicarboxylic acids such as isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, and 4,4'-dicarboxylic acid diphenyl ether; C4-16 alkane dicarboxylic acids such as succinic acid, adipic acid, azelaic acid, and sebacic acid; and C5-10 cycloalkane dicarboxylic acids such as cyclohexane dicarboxylic acid; as well as ester-forming derivatives of these dicarboxylic acid components (C1-6 alkyl ester derivatives, acyl halides, etc.). These dicarboxylic acid components can be used alone or in combination of two or more.
[0032] Among these dicarboxylic acid components, more preferred are C8-12 aromatic dicarboxylic acids such as isophthalic acid, and C6-12 alkane dicarboxylic acids such as adipic acid, azelaic acid, and sebacic acid.
[0033] In PBT resin, diol components other than 1,4-butanediol (comonomer components) include, for example, C2-10 alkylene glycols such as ethylene glycol, propylene glycol, trimethylene glycol, 1,3-butanediol, hexanediol, neopentyl glycol, and 1,3-octanediol; polyoxyalkylene glycols such as diethylene glycol, triethylene glycol, and dipropylene glycol; alicyclic glycols such as cyclohexanediol and hydrogenated bisphenol A; aromatic glycols such as bisphenol A and 4,4'-dihydroxybiphenyl; 2-molar adducts of bisphenol A in ethylene oxide and 3-molar adducts of bisphenol A in propylene oxide; C2-4 alkylene oxide adducts of bisphenol A; or ester-forming derivatives of these diols (acetylation compounds, etc.). These diol components can be used alone or in combination of two or more.
[0034] Among these diol components, more preferred are C2-6 alkylene glycols such as ethylene glycol and trimethylene glycol, polyoxyalkylene glycols such as diethylene glycol, or alicyclic diols such as cyclohexanediol.
[0035] Other comonomers that can be used besides dicarboxylic acid and diol components include, for example, aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, and 4-carboxy-4'-hydroxybiphenyl; aliphatic hydroxycarboxylic acids such as glycolic acid and hydroxyhexanoic acid; C3-12 lactones such as propiolactone, butyrolactone, valproic acid, and caprolactone (ε-caprolactone, etc.); and ester-forming derivatives (C1-6 alkyl ester derivatives, acyl halides, acetylation, etc.) of their comonomer components.
[0036] (Polyaryl sulfide resin)
[0037] PAS resin has the following characteristics: excellent mechanical properties, electrical properties, heat resistance, and other physical and chemical properties, and good processability.
[0038] PAS resin is mainly composed of a polymeric compound consisting of -(Ar-S)- (where Ar is an aryl group) as repeating units. In this embodiment, PAS resin with a commonly known molecular structure can be used.
[0039] Examples of the aforementioned arylene groups include, for example, p-phenylene, m-phenylene, o-phenylene, substituted phenylene, p,p'-diphenylene sulfone, p,p'-biphenylene, p,p'-diphenylene ether, p,p'-diphenylene carbonyl, and naphthyl. The PAS resin can be a homopolymer composed solely of the aforementioned repeating units, but copolymers containing different types of repeating units are also preferred from a processability perspective.
[0040] As a homopolymer, a polyphenylene sulfide resin using p-phenylene as the repeating unit and p-phenylene sulfide group as the arylene group is preferred. Furthermore, as a copolymer, two or more combinations of different arylene sulfide groups composed of the aforementioned arylene groups can be used, with combinations containing both p-phenylene sulfide and m-phenylene sulfide groups being particularly preferred. A composition containing 70 mol% or more, preferably 80 mol% or more, of p-phenylene sulfide groups is appropriate from the viewpoint of physical properties such as heat resistance, moldability, and mechanical properties. Moreover, among these PAS resins, a high molecular weight polymer with a substantially linear structure obtained by polycondensation of monomers mainly composed of difunctional halogenated aromatic compounds is particularly preferred. Additionally, the PAS resin used in this embodiment can also be used by mixing two or more PAS resins with different molecular weights.
[0041] In addition to linear PAS resins, other polymers that improve their molding processability include polymers that, during polycondensation, use a small amount of monomers such as polyhalogenated aromatic compounds with three or more halogen substituents, and heat low molecular weight linear polymers with branched or cross-linked structures at high temperatures in the presence of oxygen, etc., and increase the melt viscosity through oxidative or thermal cross-linking.
[0042] Including the aforementioned mixing system, it is preferable to use the PAS resin used as the matrix resin in this embodiment with a melt viscosity (310°C, shear rate 1216 sec). -1 The resin has a strength of 5–100 Pa·s.
[0043] [Carbon Black]
[0044] The carbon black involved in this embodiment has a primary particle size of 20-40 nm and a DBP oil absorption of 100 cm³. 3 The carbon black content is 100g or more. Furthermore, it contains 0.1 to 0.4 parts by weight of this carbon black relative to 100 parts by weight of thermoplastic aromatic resin. In this embodiment, by containing a specific amount of the aforementioned specific carbon black, both laser weldability and laser marking capability can be simultaneously achieved.
[0045] In this embodiment, the molded article exhibits a black color scheme by containing carbon black. Furthermore, in laser marking, the laser beam irradiation area decomposes, sublimates, and decolorizes the carbon black, thereby increasing the color difference (brightness ratio) between the laser beam irradiation area and the non-irradiated area (which has a black color scheme), thus achieving sufficient visibility. Therefore, in laser marking, to obtain sufficient visibility, it is important to use carbon black that can be colored to a black color with a small amount added and that is easily decomposed and sublimated by laser beam irradiation.
[0046] On the other hand, in laser welding, to efficiently exothermic and melt the resin, the carbon black needs to absorb the laser beam through coloration. Therefore, simply pursuing the ease of carbon black sublimation may not always yield sufficient laser weldability. This is because premature sublimation of the carbon black prevents the achievement of the required level of exothermic reaction for welding. In other words, even carbon black suitable for laser marking may not be suitable for laser welding. Therefore, in this embodiment, by specifying the primary particle size, DBP oil absorption, and content of the carbon black as described above, both laser marking and laser weldability are simultaneously achieved.
[0047] In this embodiment, the primary particle size of the carbon black is 20–40 nm. When the primary particle size of the carbon black is less than 20 nm, it is difficult to induce sublimation by laser beam irradiation, resulting in insufficient decolorization and poor visibility of the laser-marked area. When the primary particle size of the carbon black exceeds 40 nm, it exhibits poor coloring properties in the black series, the blackness of the molded product (before marking) decreases (whiteness increases), the brightness ratio between the laser-marked area and other areas decreases, and thus visibility is poor. The primary particle size of the carbon black is preferably 20–40 nm, more preferably 20–35 nm. In addition, the primary particle size in this embodiment refers to the average value obtained by measuring 3,000 unit particle sizes from an enlarged image obtained according to the ASTM D3849 standard.
[0048] On the other hand, DBP oil absorption is an indicator related to the size of the carbon black structure; a larger value reflects a larger carbon black structure. Furthermore, in this embodiment, the DBP oil absorption of the carbon black is 100 cm³. 3 / 100g or more, but less than 100cm 3 A weight of 100g or less will result in insufficient heat release from the laser beam, leading to poor laser welding and laser marking performance. The optimal oil absorption capacity for the DBP is 110cm³. 3 / 100g or more, preferably 120cm 3 / 100g, further preferably 150cm 3 / 100g. Although there is no particular upper limit to the oil absorption capacity of DBP, if the structure is too large, manufacturing itself becomes difficult, which in turn becomes disadvantageous in terms of availability. Therefore, the oil absorption capacity of DBP is preferably 600cm³. 3 / less than 100g, more preferably 500cm 3 / less than 100g, further preferably 400cm 3 / less than 100g (e.g., 300cm) 3 (less than 100g). Furthermore, the DBP oil absorption rate in this embodiment refers to the value measured based on JIS K6217-4:2008.
[0049] Although carbon black is known to include furnace black, acetylene black, and Ketjen black, Ketjen black is preferred because of its porosity and large specific surface area, which makes it easy to sublimate.
[0050] In this embodiment, 0.1 to 0.4 parts by weight of carbon black are contained relative to 100 parts by weight of thermoplastic aromatic resin. If the carbon black content is less than 0.1 parts by weight, the brightness ratio between the laser-irradiated and unirradiated areas is small during laser marking, resulting in poor laser marking performance. Furthermore, it is difficult to ensure sufficient heat release during laser welding, leading to insufficient bond strength. When the carbon black content exceeds 0.4 parts by weight, the heat release generated by the laser beam irradiation required for carbon black sublimation during laser marking increases. As a result, carbonization and discoloration of the resin portion occur, further reducing the brightness ratio between the resin portion and the unirradiated area, thus worsening visibility.
[0051] Here, it is also possible to ensure sufficient laser weldability by reducing the carbon black content and increasing the laser beam output. However, when the laser beam output is increased, if there are foreign objects in the molded part on the laser beam transmission side during laser welding, these foreign objects may release heat due to the high-output laser beam irradiation, causing the area around the foreign object to melt or foam. Therefore, it is preferable not to excessively increase the laser beam output for stable production. Moreover, in order to ensure the heat release required for resin melting with a low-output laser beam, it is preferable to increase the carbon black content to a certain extent so that the molded part on the laser beam absorption side can absorb the laser beam efficiently. However, when the carbon black content is increased too much, the heat release generated by the laser beam irradiation required for carbon black sublimation during laser marking will increase, which may easily lead to reduced visibility due to carbonization and discoloration of the resin. Here, in this embodiment, the carbon black content is set within the above-mentioned numerical range.
[0052] [Inorganic filler materials]
[0053] In this embodiment, the molded article preferably contains an inorganic filler material to improve heat resistance and mechanical strength. The type of inorganic filler material is not particularly limited as long as it does not impair the effects of this application; examples include glass fiber, glass flakes, glass beads, silica, talc, and mica, with glass fiber being particularly preferred. The fiber length of the glass fiber (its state before being prepared into a composition by melt mixing or other methods) is preferably 1 to 10 mm, and the diameter of the glass fiber is preferably 5 to 20 μm.
[0054] In this embodiment, the inorganic filler fiber is preferably contained in 20 to 200 parts by weight, and more preferably in 30 to 150 parts by weight, relative to 100 parts by weight of thermoplastic aromatic resin, from the viewpoint of improving heat resistance and mechanical strength.
[0055] [Elastomer]
[0056] The molded article of this embodiment preferably contains an elastomer to improve impact resistance. Examples of such elastomers include olefin-based elastomers, vinyl chloride-based elastomers, styrene-based elastomers, polyester-based elastomers, butadiene-based elastomers, acrylic rubber-based elastomers, urethane-based elastomers, polyamide-based elastomers, and silicone-based elastomers. Specifically, ethylene ethyl acrylate (EEA), methacrylate-butene-styrene (MBS), ethylene glycidyl methacrylate (EGMA), and polytetramethylene glycol (PTMG)-based polyester elastomers may be used.
[0057] In this embodiment, from the viewpoint of improving impact resistance, the elastomer preferably contains 5 to 30 parts by weight, and more preferably 10 to 20 parts by weight, relative to 100 parts by weight of thermoplastic aromatic resin.
[0058] [Other ingredients]
[0059] In this embodiment, in addition to the above-mentioned components, known additives commonly added to thermoplastic resins and thermosetting resins may also be used, such as burr inhibitors, mold release agents, lubricants, plasticizers, flame retardants, dyes, pigments and other colorants, crystallization promoters, crystallization nucleating agents, various antioxidants, heat stabilizers, weather stabilizers, and preservatives, without impairing their effects.
[0060] The molded article of this embodiment is formed by molding the resin composition described above. The method for producing the molded article of this embodiment is not particularly limited, and known methods can be used. For example, it can be produced by feeding the resin composition described above into an extruder for melt mixing and granulation, and then feeding the granules into an injection molding machine equipped with a specified metal mold for injection molding.
[0061] Next, we will explain laser welding and laser marking in turn.
[0062] [Laser Welding]
[0063] As described above, laser welding involves overlapping a molded article made of a material that is transmissive to laser beams (laser beam transmitting side) with a molded article made of a material that absorbs laser beams (laser beam absorbing side). Then, a laser beam is irradiated from the transmissive molded article side, causing heat to be released at the interface with the laser beam absorbing molded article, thus performing welding. Furthermore, the molded article in this embodiment is for the laser beam absorbing side. That is, during laser welding, a separate molded article for the laser beam transmitting side is prepared, and the molded article of this embodiment and the molded article for the laser beam transmitting side are overlapped such that their surfaces to be welded are in contact with each other, and a laser beam is irradiated from the transmissive molded article side to perform welding.
[0064] In this embodiment, laser beams in the near-infrared region can be cited as examples of laser beams that can be used for laser welding. Among near-infrared laser beams, lasers emitting wavelengths of 900–1200 nm are particularly preferred, and semiconductor lasers and YAG lasers are preferred.
[0065] During laser welding, the irradiation conditions of the laser beam are not particularly limited; they can be adjusted appropriately based on the combination of materials used and the shape of the molded product. These irradiation conditions need to be set to provide the energy required for melting the interface between the laser beam-through side and the laser beam-absorbing side of the molded product. In particular, the appropriate range of conditions can be varied depending on the laser beam transmittance and thickness of the laser beam-through side of the molded product. Those skilled in the art can determine the appropriate conditions by considering the specifications of their available equipment and primarily through a limited number of trials involving variations in the laser beam output and irradiation time (scanning speed).
[0066] As an example, the laser beam-transmitting side molded product uses a 1mm thick PBT resin molded product with a transmittance of 40% for a 940nm laser beam, while the laser beam-absorbing side molded product uses a PBT resin molded product containing 0.2% by mass carbon black. Furthermore, when laser welding is performed by irradiating a 940nm laser beam at a scanning speed of 10mm / sec, the output can be set to approximately 5W to 15W.
[0067] In addition, in order to suppress the occurrence of the following adverse conditions, it is preferable to set the output and irradiation time to a low level so that the irradiation energy does not become too high. That is, the adverse conditions are unexpected melting and foaming of the welded part caused by foreign objects or the like inside the molded part on the side through which the laser beam passes, as described above.
[0068] [Laser Marking]
[0069] As described above, laser marking is performed by irradiating the molded article of this embodiment with a laser beam to decompose, sublimate, and decolorize the carbon black contained in the molded article. Therefore, when laser marking is performed on the molded article of this embodiment, the laser beam is scanned and irradiated in a manner that depicts the text or graphics to be marked. Alternatively, the laser beam can be irradiated comprehensively by placing a mask layer between the light source and the molded article so that the laser beam only reaches the part to be marked. The text or graphics depicted are not particularly limited and can be arbitrarily selected.
[0070] Examples of laser beams used in laser welding include Nd:YAG lasers and Nd:YVO4 lasers.
[0071] Furthermore, during laser marking, the irradiation conditions of the laser beam are not particularly limited; they can be appropriately adjusted based on the concentration of carbon black in the material of the molded article and the heat resistance of the resin. These irradiation conditions need to be set such that the carbon black can decompose and sublimate to decolorize the molded article. As mentioned above, when the heat generated by the laser beam irradiation becomes excessive, visibility will decrease due to resin carbonization and discoloration; therefore, it is preferable to suppress the irradiation energy to prevent it from becoming too high. Specifically, the energy can be adjusted mainly by changing the laser beam output, irradiation time (scanning speed), and frequency. Since these can be easily changed by adjusting the settings of the irradiation device, those skilled in the art can consider the specifications of their available device and find suitable conditions through a limited number of trials with different combinations.
[0072] As an example, using particles with a primary particle size of 21 nm and a DBP oil absorption capacity of 175 cm³ 3 / 100g of carbon black 0.2% by mass of PBT resin molded product, and when laser marking is performed by irradiating a laser beam with a wavelength of 1064nm with an output of 2W and a Q switching frequency of 20kHz, the scanning speed can be set to about 200-700mm / sec.
[0073] Example
[0074] The following examples will further illustrate this embodiment in detail, but this embodiment is not limited to the following examples.
[0075] [Examples 1-4, Comparative Examples 1-6]
[0076] In each embodiment and comparative example, PBT resin, carbon black, elastomer, and glass fiber were mixed and stirred in the proportions (parts by weight) shown in Table 1 to prepare resin compositions. Details of each component shown in Table 1 will be shown below.
[0077] PBT resin: (manufactured by Wintech Polymer Co., Ltd., intrinsic viscosity (IV) = 0.88 dL / g, CEG = 16 meq / kg)
[0078] Carbon Black 1: (Made by Mitsubishi Chemical Corporation, furnace black, primary particle size 22nm, DBP oil absorption 116cm³) 3 / 100g)
[0079] Carbon Black 2: (Made by Mitsubishi Chemical Corporation, furnace black, primary particle size 21nm, DBP oil absorption 175cm³) 3 / 100g)
[0080] Carbon Black 3: (Lion Professional Chemical Co., Ltd., Ketjen Black, primary particle size 30nm, DBP oil absorption 396cm³) 3 / 100g)
[0081] Carbon Black 4: (Made by Mitsubishi Chemical Corporation, furnace black, primary particle size 15nm, DBP oil absorption 48cm³) 3 / 100g)
[0082] Carbon Black 5: (Made by Mitsubishi Chemical Corporation, furnace black, primary particle size 16nm, DBP oil absorption 62cm³) 3 / 100g)
[0083] Carbon Black 6: (Made by Mitsubishi Chemical Corporation, furnace black, primary particle size 24nm, DBP oil absorption 42cm³) 3 / 100g)
[0084] Carbon Black 7: (Made by Mitsubishi Chemical Corporation, furnace black, primary particle size 50nm, DBP oil absorption 115cm³) 3 / 100g)
[0085] Elastomer: (NUC Corporation, NUC-6570 (ethylene-ethyl acrylate copolymer))
[0086] Glass fiber: (manufactured by Nippon Electric Glass Co., Ltd., ECS03T-187, average fiber diameter 13μm, average fiber length 3mm)
[0087] The primary particle size of carbon black 1 to 7 and the oil absorption of DBP are shown in Table 2 below.
[0088] [Table 1]
[0089]
[0090] [Table 2]
[0091]
[0092] [evaluate]
[0093] The obtained resin composition was used to produce a flat molded article of 70mm×50mm×3mm, and the laser marking was evaluated.
[0094] (1) Laser marking performance (brightness ratio)
[0095] Laser marking was performed on the obtained molded parts using a combination of scanning speed and Q-switching frequency conditions shown below. After laser marking, images of the marked and unmarked areas were scanned using a Canon LiDE 210 scanner, and the brightness of the histograms was obtained using Adobe Photoshop Elements. Furthermore, the brightness ratio (highest brightness value of the marked area ÷ brightness value of the unmarked area) was calculated based on the highest brightness value of the marked area and the brightness value of the unmarked area. The measurement results are shown in Table 1.
[0096] (Laser marking conditions)
[0097] Laser marking equipment: KEYENCE, MD-V9900A
[0098] Laser type: Nd:YVO4 laser, wavelength 1064nm
[0099] Q switching frequency: 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100Hz
[0100] Laser output: 2W
[0101] Scanning speeds: 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000 mm / s
[0102] (2) L value (brightness) of the molded product
[0103] The L value was measured using a Spectrophotometer SE6000 manufactured by Nippon Denshoku Kogyo Co., Ltd., relative to the molded product. The measurement results are shown in Table 1.
[0104] (3) Laser welding strength
[0105] Using the molded article as the laser beam absorption side and a strip-shaped molded article of 80mm × 20mm × 1mm made by Wintech Polymers Co., Ltd. (DURANEX 3300EF2001, a colorless PBT resin composition containing 30% by mass glass fiber) as the laser beam transmission side, the two were overlapped. Then, in this state, laser welding was performed under the laser welding conditions shown below. Next, the breaking strength was determined using a Shimadzu Autograph AG-X universal testing machine at a test speed of 10mm / min, and the weld strength was calculated. The results are shown in Table 1.
[0106] (Laser welding conditions)
[0107] Laser welding equipment: FINEDEVICE CO.,LTD.FD-2430
[0108] Laser type: Nd:YAG laser (wavelength: 940nm)
[0109] Irradiation speed: 10mm / sec
[0110] Irradiation diameter: φ1.6mm
[0111] Irradiation distance: 4mm
[0112] Laser output: 5W~13W
[0113] Furthermore, "laser output: 5W to 13W" refers to the condition under which the highest bonding strength is obtained when performing laser welding under various conditions with output varying from 5W to 13W in each embodiment. This is because, as mentioned above, depending on the laser beam irradiation conditions, excessive decomposition of the carbon black contained in the molded part on the laser beam absorption side makes it difficult to obtain the heat release required for laser welding. In this respect, the optimal laser irradiation conditions for laser welding will vary depending on the material.
[0114] According to Table 1, the molded articles of Examples 1-4 exhibit a high average brightness ratio and good laser marking properties. Furthermore, it was also found that the laser welding strength was excellent, and both laser marking and laser welding properties could be achieved simultaneously. In contrast, in Comparative Examples 1-6, at least one of the laser marking properties and laser welding strength was poor, making it impossible to achieve these properties simultaneously.
Claims
1. A molded article that can be used on the laser beam absorption side during laser welding, and can be marked by irradiating a laser beam. The molded article is formed from a resin composition, and the resin composition contains, relative to 100 parts by weight of thermoplastic aromatic resin, a primary particle size of 20-35 nm and a DBP oil absorption of 150 cm³. 3 / 100g or more 600cm 3 0.17 to 0.25 parts by weight of carbon black per 100g or less.
2. The molded article according to claim 1, wherein, The thermoplastic aromatic resin is polybutylene terephthalate resin or polyarylene sulfide resin.
3. The molded article according to claim 1 or 2, wherein, Relative to 100 parts by weight of the thermoplastic aromatic resin, the resin composition further contains 20 to 200 parts by weight of inorganic filler and 10 to 30 parts by weight of elastomer.
Citation Information
Patent Citations
Resin composition suitable for laser welding application having resin and laser beam transmitting colorant, and having transmission rate ratio (t black resin for laser transmission / t natural resin) of 0.5-1.2
JP2008024946A
Laser etching master batch for light color identification, preparation method thereof and application
CN104448531A
Moulding materials for use in motor vehicle interiors
CN1345354A
White coloring laser-marking thermoplastic resin composition
CN1500831A
Resin composition for laser marking, laser marking and laser-marked molded product
JP1999140284A